Building the Clinical Bridge to Advance Education, Research, and Practice Excellence - Marilyn Svejda; Janet Goldberg; Maureen Belden; Kathleen Potempa; Margaret Calarco (Hindawi Limited, 2012)
The University of Michigan School of Nursing and the Health System partnered to develop an undergraduate clinical education model as part of a larger project to advance clinical education, practice, and scholarship with education serving as the clinical bridge that anchors all three areas. The clinical model includes clusters of clinical units as the clinical home for four years of a student's education, clinical instruction through team mentorship, clinical immersion, special skills preparation, and student portfolio. The model was examined during a one-year pilot with junior students. Stakeholders were largely positive. Findings showed that Clinical Faculty engaged in more role modeling of teaching strategies as Mentors assumed more direct teaching used more clinical reasoning strategies. Students reported increased confidence and competence in clinical care by being integrated into the team and the Mentor's assignment. Two new full time faculty roles in the Health System support education, practice, and research.